PENGARUH FINANCIAL KNOWLEDGE, FINANCIAL ATTITUDE DAN INTERNAL LOCUS OF CONTROL TERHADAP PERILAKU MANAJEMEN KEUANGAN - Nurul Rohmah; Arik Susbiyani; Rendy Mirwan Aspirandy; Dwi Cahyono (Jurnal Ekobis : Ekonomi Bisnis & Manajemen, 2021)
This study aims to determine whether the behavior of financial management on MSME actors can be measured or influenced by several factors that have been proposed in this study, namely financial knowledge, financial attitude and internal locus of control . The factors proposed are factors that may have an influence on financial management behavior on the object of research. The population in this study were MSMEs in the food sector in Genteng District, Banyuwangi Regency and the sample in this study amounted to 60 MSMEs in the food sector, Genteng District, Banyuwangi Regency which were taken through purposive sampling method .  Based on t test results, financial knowledge has no significant effect on the behavior of financial management in SMEs in the field of food District of tiles, Banyuwangi. The financial attitude and internal locus of control factors have a significant influence on the behavior of financial management on MSME actors in the food sector, Genteng District, Banyuwangi Regency.Keywords : Financial Knowledge, Financial Attitude, Internal locus of Control, Financial Management Behavior